STRATEGI KOMUNIKASI PUBLIC RELATIONS - Artis Artis (Lembaga penelitian dan pengabdian kepada Masyarakat, 2011)
Living man in interrelates society. Relationship among human being done by gets communication so man one by another one mutually understand and influence regard for the benefit, it that always been practiced by Public Relations( liaison) in a governance and also firm institute to reach to the effect which ices. The institute of Public Relations declares for,”Public Relations is overall effort which be passed off by design and berkesenambungan in order to creates and pet keenness and mutual understanding among an organization with whole its member “. In this case, Public Relations in give distribution on manajement's strategy there is two: First, Doing task as part of Public Relations's strategy and involvement in comprehensive process and gives benefit for management an organization. Both of, Public Relations gets role in management strategy in bring off activity to reach to the effect good one gets internal character and also external one correspond to that desirable by good institute on level governance and firm.